Predictors of Students’ Proper Waste Disposal Behavior in School Environment: a Partial Least Squares Structural Equation Modeling Approach - Meradios, John Kenneth; Manglicmot, Kayzel (East Asian Journal of Multidisciplinary Research, 2024)
It is evident from various reports and statistics that there is a significant gap between the desired environmental state and the current situation, primarily due to improper waste disposal. This study used a predictive-correlational design and structural equation modeling to examine the predictors of proper waste disposal behavior. The research instrument was validated and used to survey 293 high school students across three public schools in Nueva Ecija, Philippines. Using WarpPLS 8.0, the results revealed that (1) accessibility of trash bins, perceived consequences, environmental concern, and perceived behavioral control predict proper waste disposal behavior, and (2) environmental concern and perceived behavioral control sequentially mediate the effect of perceived behavioral control on proper disposal behavior. This study proposes a structural model with meaningful predictive accuracy that can help educational institutions design effective waste management programs empowering education to promote eco-friendly behavior. Future studies may be conducted to test the revised model presented in this study.